The Barriers to Caring for a Child Living with Cerebral Palsy (CP) in Rural Limpopo, South Africa - Ngokwana Rachamose; Clare Harvey (Disabilities)
Maternal primary caregivers in rural low-income contexts who care for children with cerebral palsy (CP) experience significant barriers related to their caregiving responsibilities that have a profound impact on all aspects of their lives. This paper reports on a study that aimed to explore barriers related to caring for a child living with CP in the rural province of Limpopo, South Africa. An exploratory qualitative research design was employed. Purposive, convenience, and snowball sampling was used to recruit 10 primary maternal caregivers of children living with CP between the ages of 3 and 18 years. A semi-structured interview was used to collect data. The data were analyzed using a thematic analysis. This study found six barriers related to caring for a child living with CP in rural areas, which included physical, financial, social, emotional, spiritual, and health barriers. The primary maternal caregivers of children living with CP in rural areas experience a significant burden of care. Consequently, they need support and respite care to ease these challenges.